The Healing Journey: Help Seeking for Self-Injury Among a Community Population. (July 2015) - Long, Maggie; Manktelow, Roger; Tracey, Anne
Help seeking is known to be a complex and difficult journey for people who self-injure. In this article, we explore the process of help seeking from the perspective of a group of people living in Northern Ireland with a history of self-injury. We conducted 10 semistructured interviews and employed a grounded theory approach to data analysis. We created two major categories from the interview transcript data: (a) "involution of feeling, " which depicts participants' perspectives on barriers to help seeking; and (b) "to be treated like a person, " in which participants communicate their experiences of help seeking. The findings pose important implications for policy, practice, theory, and future research, including the need to increase the uptake of follow-up care among people who arrive at hospitals as a result of self-injury, self-harm, or suicidal behaviors.